Sleep Disturbances and Patterns in Children With Neurodevelopmental Conditions - Halstead, Elizabeth J.; Joyce, Anna; Sullivan, Emma; Tywyn, Carwyn; Davies, Kyle; Jones, Alexandra; Dimitriou, Dagmara (Frontiers in Pediatrics, 2021)
Background: Children with neurodevelopmental conditions (NDC) often experience sleep problems which are long-lasting and more complex than typically developing children. These sleep problems impact their families and there is little guidance for management specifically for sleep for families of children with neurodevelopmental conditions. Methods: Data on 601 children aged between 2-17 years was analysed from a UK non-profit service for sleep for families of children with NDC. Parents/carers completed the children’s sleep habit questionnaire, a 7 day sleep diary, and information on child age, diagnosis and medication. Parents also reported previous sleep management techniques they had tried. Results: Overall, we found differences between age, diagnosis, and medication use groups for sleep disturbances and sleep diary parameters in these populations. Sensory conditions were associated with high night time waking duration. Parents reported their child’s short sleep duration was the most common problem for them. Conclusions: Key areas for further research are outlined including, the long term considerations for parental presence at bedtime for sleep anxiety, melatonin use and efficacy, and consideration for interventions to reduce daytime fatigue in children aged 7-11 years old.